Comparative Analysis of Microbial Community Diversity and Dynamics on Diseased Tubers During Potato Storage in Different Regions of Qinghai China - Xie, Tianyan; Shen, Shuo; Hao, Yufan; Li, Wei; Wang, Jian (Frontiers in Genetics, 2022)
Effective storage of potatoes is very important for the food industry. Given the problems involving rotten potatoes and low quality during storage, harvested potatoes from the main potato-producing areas in the Qinghai Plateau were treated by selection and air drying (Group “A”) and the others were stored directly as controls (Group “C”). Then, the microbial community structure and diversity of diseased potato tubers from four main production areas were analyzed by high-throughput sequencing technology in different storage stages. The results showed that the community composition and diversity of microbes in different regions and storage periods were different, and the dominant fungi in diseased potato tubers were Boeremia in Huangyuan( HY), Maying( MY) and Zhongling( ZL) and Apiotrichum in Huangzhong( HZ) at the genus level. The dominant bacterial genus was Pseudomonas, but its abundance varied in samples from different regions and storage periods. In the analysis of indicator species, there were some common species and endemic species in each region and period, and the period with the largest number of different species was the third period. Among the four storage periods, the region with the largest number of different species was HZ. Some fungi, especially Fusarium and other potato pathogens, were more abundant in control Group “C” than in treatment Group “A”. In the diversity analysis, the α diversity of fungi in Group “C” was higher than that in Group “A”, but the α diversity of bacteria in Group “A” was higher than that in Group “C”, and there was no obvious regularity with storage time. The β diversity varied significantly among different regions. In addition, through functional prediction analysis, it was found that a plant pathogen was one of the main nutritional types of fungi, which indicated that treatment by selection and drying could significantly reduce phytopathogenic microbe and other microorganisms and could be used as an effective measure for potato storage compared with the prevention and control by drugs that can cause environmental pollution. This study may provide a theoretical basis for biological control of potato cellar diseases and the maintenance of potato quality during long-term storage.